Creating the perfect design brief : how to manage design for strategic advantage - Phillips, Peter L., ....- (New York : Allworth Press, 2012)
In the only book of its kind, now revised and updated with the latest research on the topic, veteran design consultant Peter L. Phillips offers the tools for success gained from nearly thirty years of developing corporate and brand identity programs. Readers will discover the most effective formats for design briefs, how to structure the best possible team, what distinguishes a great design brief from an adequate one, how to use the brief in project tracking, as a measuring tool, as a means of getting approval for a design solution, and much, much more. By covering all of the essential elements of an effective design brief, this unique and empowering guide will help you to ensure that the goals of your corporate design strategy are met.
Includes bibliographical references (pages 206-207) and index.
Keywords: Production planning; Work design